DNA Methylation Changes in Tbx3 in a Mouse Model Exposed to Polybrominated Diphenyl Ethers. (May 2017) - Shimbo, Takashi; Dunnick, June K.; Brix, Amy; Mav, Deepak; Shah, Ruchir; Roberts, John D.; Wade, Paul A.
DE-71, a commercial mixture of polybrominated diphenyl ethers widely used in flame retardants, is a pervasive environmental contaminant due to its continuing release from waste material and its long half-life in humans. Although the genotoxic potential of DE-71 appears to be low based on bacterial mutagenicity, it remains a public health concern due to its reported involvement in tumor development. Molecular mechanisms by which DE-71 influences tumor incidence or progression remain understudied. We used liver carcinoma tissue from mice exposed to DE-71 to test the hypothesis that epigenetic alterations consistent with tumor development, specifically DNA methylation, result from long-term DE-71 exposure. We profiled DNA methylation status using the methylated-CpG island recovery assay coupled with microarray analysis of hepatocellular carcinoma DNA from animals exposed to DE-71. DE-71 exposure had little impact on global DNA methylation. However, we detected gene body–specific hypomethylation within the Tbx3 locus, a transcription factor important in liver tumorigenesis and in embryonic and cancer stem cell proliferation. This nonpromoter hypomethylation was accompanied by upregulation of Tbx3 mRNA and protein and by alterations in downstream cell cycle–associated marker expression. Thus, exposure to DE-71 may facilitate tumor development by inducing epigenetic programs that favor expansion of progenitor cell populations.